Follicular Graft Vs Host Reaction: A Rare Presentation - Vashisht, Deepak (Indian Dermatol Online J, 2020)
Graft versus host disease (GVHD) is a unique entity wherein the donated marrow cells (graft) view the hosts as foreign and attack various body organs. Skin is the most frequently affected organ followed by mucosa, eyes, gastrointestinal, respiratory, musculoskeletal system, and other organs. The incidence of GVHD varies from 25 to 80%. Cutaneous involvement can present as exanthem, epidermolysis, lichenoid eruptions, erythroderma, ichthyosis, pityriasis rubra pilaris like lesions, psoriasiform lesions or just pruritus. Asymptomatic truncal follicular eruptions as the major presentation is rare. We report a case of aplastic anemia that developed extensive truncal folliculocentric papules 10 months following an allogeneic hematopoietic stem cell transplantation. Histopathological examination of the follicular lesions revealed perifollicular inflammatory infiltrate comprising of lymphocytes, plasma cells and histiocytes at the dermo-epidermal junction. Basal cell vacuolization, pigment incontinence in the upper dermis and few apoptotic keratinocytes in the follicular epidermis were also seen. The patient responded satisfactorily to tapering doses of steroids.